Analisis Pengaruh Degradasi Parameter Geoteknik akibat Air terhadap Mining Recovery di Pit 1 PT Bukit Asam Tbk - Wibowo, Vinaldo; Yusuf, Maulana; Toha, Taufik (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This research was conducted with a back analysis on the pit 1 slopes of PT Bukit Asam, TBK where material deformation occurred due to saturation from material above the slope that previously contained a settling pond holding water from other pits. Slope stability analysis is necessary to achieve a stable slope geometry with FoS >1.25. The analysis performed for determining this FoS involves back analysis to obtain stable slope geometry and to calculate changes in coal recovery due to geometric changes in the excavation slope. This study aims to analyze slope stability to obtain actual geotechnical parameters in the excavation slopes affected by water and their safety factors, as well as to analyze changes in mining recovery due to changes in slope geometry. Slope stability determination is carried out by conducting analysis. This research aims to analyze slope stability to obtain actual geotechnical parameters in excavated slopes influenced by water and their safety factors, as well as to conduct an analysis to determine changes in mining recovery due to changes in slope geometry. The determination of slope stability is carried out by performing a back analysis on the excavated slopes that have experienced deformation, resulting in new geotechnical parameters that have been degraded. The degradation of geotechnical parameters on the slope of Pit 1 excavation resulted in a decrease in cohesion (C) by 63% from 77.14 Kpa to 28.26 Kpa, and the internal friction angle (Ǿ) decreased by 32% from 27.16° to 18.35°. The degradation of geotechnical parameters on the slope of Pit 1 caused a mining recovery decrease of 61.7%, where the initial pit slope plan of Pit 1 was expected to yield 4,750,000 tons of coal, while the revised pit slope plan of Pit 1 yielded 2,820,000 tons of coal.